Heavy Metals in the Vegetables Collected from Production Sites - Hassan Taghipour; Mohammad Mosaferi (Tabriz University of Medical Sciences, 2013)
Background: Contamination of vegetable crops (as an important part of people's diet) with heavy metals is a health concern. Therefore, monitoring levels of heavy metals in vegetables can provide useful information for promoting food safety. The present study was carried out in north-west of Iran (Tabriz) on the content of heavy metals in vegetable crops. Methods: Samples of vegetables including kurrat (n=20) (Allium ampeloprasumssp. Persicum), onion (n=20) (Allium cepa) and tomato (n=18) (Lycopersiconesculentum var. esculentum), were collected from production sites in west of Tabriz and analyzed for presence of Cd, Cr, Cu, Ni, Pb and Zn by atomic absorption spectroscopy (AAS) after extraction by aqua regia method (drying, grounding and acid digestion). Results: Mean ± SD (mg/kg DW) concentrations of Cd, Cu, Cr, Ni and Zn were 0.32 ± 0.58, 28.86 ± 28.79, 1.75 ± 2.05, 6.37± 5.61 and 58.01 ± 27.45, respectively. Cr, Cu and Zn were present in all the samples and the highest concentrations were observed in kurrat (leek). Levels of Cd, Cr and Cu were higher than the acceptable limits. There was significant difference in levels of Cr (P<0.05) and Zn (P<0.001) among the studied vegetables. Positive correlation was observed between Cd:Cu (R=0.659, P<0.001) Cr:Ni (R=0.326, P<0.05) and Cr:Zn (R=0.308, P<0.05). Conclusion: Level of heavy metals in some of the analyzed vegetables, especially kurrat samples, was higher than the standard levels. Considering the possible health outcomes due to the consumption of contaminated vegetables, it is required to take proper actions for avoiding people's chronic exposure.